Спектральні характеристики лінійних фотонно-кристалічних хвилеводів - Букреєва, В. І. (ХНУРЕ, 2020)
Modeling of two schemes of linear photonic crystal waveguides is performed with using of packages MIT Photonic Bands and MEEP. Spectral characteristics and dispersion diagrams are obtained on the basis of numerical calculations. It is shown that hollow and dielectric waveguide channels have different spectral characteristics.
Keywords: фотонно-кристалічний хвилевід; коефіцієнт пропускання; фотонна заборонена зона; дисперсійна діаграма